Analysis Of Training Effectiveness In Improving Employee Performance At My Dormy Hostel Umm: Senior And Junior Employees Perspectives(Case Sub My Dormy Hostel Umm) - Nofa Suci Agustina; R. Iqbal Robbie; Immanuel Mu’ammal (International Journal of Entrepreneurship and Tourism, 2025)
This study analyzes the effectiveness of training in improving employee performance at My Dormy Hostel UMM, considering the perspectives of both senior and junior employees. In the competitive hospitality industry, training plays a crucial role in enhancing productivity, work efficiency, and service quality for customers. This research adopts a qualitative approach using interviews, observations, and documentation to gather comprehensive data. The findings indicate that on-the-job training is more effective than theory-based training, as it provides hands-on experience in a real work environment. Additionally, the involvement of senior employees as mentors in training has proven to help junior employees adapt and understand the company's work culture. However, several challenges remain, such as the lack of a systematic evaluation of training effectiveness and gaps between the provided training materials and real work conditions. Therefore, it is recommended that My Dormy Hostel UMM develop a more structured and relevant training program, tailor materials to the specific needs of each employee group, and enhance post-training evaluation systems to ensure optimal implementation in improving employee performance.